Le diagnostic socio-économique des DOCOB, un outil pour renforcer l’ancrage territorial des sites Natura 2000 - Christelle Audouit; Christelle Hinnewinkel; Paul Sauboua; Alejandro Barrera de Paz; Philippe Chagnon; Daphné Menthonnex (VertigO)
The OFB (Office français pour la biodiversité) is heavily involved in the implementation of the Natura 2000’ directives at sea. The OFB is the coordinator or co-coordinator of more than a hundred Natura 2000 sites at sea and supports other managers in their coordination. In order to promote the management of these sites and in a dialogue with its partners, the OFB wishes to better identify and, if necessary, develop the local foothold of Natura 2000 sites, starting with the drafting phase of the socio-economic diagnosis of the management plan for Natura 2000 sites. This desire to strengthen the local foothold of a site requires particular attention to the relations between stakeholders, their representations of the site's species and habitats, and their involvement in protecting them. This study is based on an analysis of 30 diagnosis to identify their strengths and limitations in these fields and thus propose tools to strengthen the role of diagnosis as a tool promoting the local foothold of Natura 2000 sites. This analysis reveals a systematic repertory of actors, a very succinct and too general description of conflicts. Moreover, it reveals that little account is taken of the users' initiatives in the Natura 2000 process and of their representations of species and habitats. Several proposals are made in this article to list the uses and activities, the past or future implications for the preservation of the environment in this diagnosis in order to promote a hybridization between the territory conceived by the Natura 2000 site and the territories experienced by the stakeholders. These proposals are the result of exchanges with managers on the tools and the methods they use. From 2019 to 2020, a manager of Natura 2000 site experimented them. This work aims to contribute to improving the methodological framework of the socio-economic diagnosis to strengthen the local foothold of Natura 2000 sites. socio-economic diagnosis, local foothold, stakeholders, involvement, social representation, protected spaces, Natura 2000, management plan